Internal Audit Profession and Financial Performance in Commercial Banks in Rwanda - Mustari, Kahambu; Rusibana, Claud; Nzamalu, Ambrose (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2020)
In all the countries in the world, commercial banks contribute greatly in the economic development of a country (Beck, Demirgüç-Kunt & Levine, 2006). Therefore, tracking the performance of commercial banks has been of great importance both for scholars and for policy makers. The main objective of this research was to investigate the role played by internal audit profession in the financial performance of commercial banks in Rwanda, taking a case of Kenya Commercial Bank, Rwanda plc. The research followed three specific objectives, namely, to investigate internal audit profession in KCB Bank Rwanda plc; to determine the level of financial performance of KCB Bank Rwanda plc and to find out the relationship between internal audit profession and financial performance of KCB Bank Rwanda plc. The research used descriptive and correlational research design with a target of 87 employees all taken as the sample for this research. Structured questionnaires were distributed to the sample and 79 were filled and returned. The collected data was analyzed using IBM SPSS version 22. The results showed that the most of the employees in KCB Bank Rwanda plc are male who represent 72.15% of the total respondents, majority of the respondents were between 31-35 years represented by 42(53.2%) of the respondents. The findings on objective one revealed that 57% of the respondents strongly agreed that audit independence is important for the internal auditing at 32.9% agreed. The findings on objective two revealed that 73.4% of the respondents indicated high level of satisfaction in terms of financial performance of the Bank. On objective three, the findings revealed that all the indicators used for measuring internal audit were positive and significantly related to ROA, ROE and interest margin (some at 5% and others at 10%), except for audit due care which was not significantly related to ROE and interest margin. The findings further revealed that the adjusted R2=0.81 for ROA, adjusted R2=0.164 for ROE and adjusted R2= 0.292 for interest margin. Further, the ANOVA analysis for ROA, ROE and interest margin revealed that all the three models were significant at 5%. The regression equations with audit independence, professional competence and audit due care as predictor variables showed that both audit independence and professional competence have positive coefficient on ROA, ROE and interest margin. The researcher highly recommends prudential adoption of internal auditing function within the banking sector. Policy makers should come up with standardized measures in relation to internal auditing. The managers should be at the forefront to ensure that the internal auditing function operates independently without managerial influences and with due diligence. This recommendation is informed by the positive effect that auditing has on the financial performance of commercial banks.